Thirst sensations and AVP responses at rest and during exercise-cold exposure - Kenefick, R. W.; Hazzard, M. P.; Mahood, N. V.; Castellani, J. W. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: The purpose of this study was to 1) determine the effect of hypohydration (HYPO) on thirst sensations during moderate exercise in the cold and 2) determine a possible mechanism for a cold-induced decline in thirst. METHODS: In the first phase of the study, eight males walked on four occasions, in T-shirts, shorts, and shoes, at 50% VO2max, for 60 min in either a 4 degrees C (cold) or 27 degrees C (temperate) environment in a state of HYPO or euhydration (EU). In the second phase, nine males in states of EU or HYPO randomly performed four trials consisting of 30 min standing at 27 degrees C, followed by 30 min of standing and 30 min of treadmill exercise at 50% of VO2max, in either 4 degrees C or 27 degrees C air. RESULTS: In phase 1, thirst sensations were lower throughout 60 min of exercise (P < 0.05) in both HYPO and EU conditions during the cold trials. In phase 2, despite elevated plasma osmolality (P < 0.05), perception of thirst and plasma arginine vasopressin [AVP] similarly decreased (P < 0.05) after 30-min standing rest and 30-min exercise in the HYPO-cold trial, compared with the HYPO-temperate, EU-cold, and EU-temperate trials. CONCLUSIONS: When either euhydrated or hypohydrated, cold exposure attenuated thirst by up to 40% at rest and during moderate-intensity exercise. The attenuated thirst when hypohydrated during cold exposure was associated with lower plasma [AVP] despite an elevated plasma osmolality. This decline in thirst and AVP in the cold may be the result of peripheral vasoconstriction, mediating an increase in central blood volume and stimulation of central volume receptors.